1999
DOI: 10.1007/s11663-999-0112-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of nucleation and supersaturation for the aluminum-deoxidation reaction in liquid iron

Abstract: The nucleation process of alumina in aluminum-deoxidized liquid iron was investigated by computer simulation, in which the Gibbs free-energy change of the parent liquid iron, the dependence of interfacial free energy between liquid iron and ␣-alumina on oxygen content, and the dependence of the interfacial free energy on the curvature of a nucleus were considered. The calculated curve of the Gibbs free-energy change of the systems (⌬G), with respect to nuclear radius, has a maximum and a minimum. Nucleation oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 11 publications
2
52
0
Order By: Relevance
“…2). 13 where subscript i means each alumina. The s Fe-i calculated from the molar enthalpies of aluminas, H i°, 14) using Eqs.…”
Section: Classical Homogeneous Nucleation Theorymentioning
confidence: 99%
See 4 more Smart Citations
“…2). 13 where subscript i means each alumina. The s Fe-i calculated from the molar enthalpies of aluminas, H i°, 14) using Eqs.…”
Section: Classical Homogeneous Nucleation Theorymentioning
confidence: 99%
“…Thus the model does not consider the free oxygen in the usual concentration ranges of oxygen and aluminum in liquid iron. In a previous report, 13) the present authors applied this model to liquid iron containing excess oxygen. The results showed that the model could be applied to liquid iron with excess oxygen and the excess oxygen should originate, partly, from the suspension of fine alumina deoxidation products and partly, from the supersaturation of alumina-associated compounds.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations